Conceptual design of an intense positron source based on an LIA - Long, Ji-Dong; Yang, Zhen; Dong, Pan; Shi, Jin-Shui (Chinese physics C, 2012)
Accelerator based positron sources are widely used due to their high intensity. Most of these accelerators are RF accelerators. An LIA （linear induction accelerator） is a kind of high current pulsed accelerator used for radiography. A conceptual design of an intense pulsed positron source based on an LIA is presented in the paper. One advantage of an LIA is its pulsed power being higher than conventional accelerators, which means a higher amount of primary electrons for positron generations per pulse. Another advantage of an LIA is that it is very suitable to decelerate the positron bunch generated by bremsstrahlung pair process due to its ability to adjustably shape the voltage pulse. By implementing LIA cavities to decelerate the positron bunch before it is moderated, the positron yield could be greatly increased. These features may make the LIA based positron source become a high intensity pulsed positron source.